PENYELESAIAN KREDIT MACET DI PD. BPR NTB MATARAM (STUDI PD. BPR NTB MATARAM) - Aghna Vitra Baradi; M. Yazid Fathoni (Private Law, 2021)
This research aims are to know the credit provision in PD. BPR NTB Mataram and its dispute settlement mechanism. This research is empirical legal research which applies statute, conceptual and sociological approaches. Source and type of legal materials are primary, secondary and tertiary legal materials which collected by library research with qualitative method. Steps of credit provision in PD. BPR Mataram are credit request submission, debtor’s data analysis, credit decision, debtor’s cash disbursement. However, the settlement of bad credit steps are collecting of debt from the debtors, sending letters of warning 1, 2 and 3 and finally, the handover the guarantee voluntarily.